PERANCANGAN GAME EDUKASI BERBASIS MOBILE PADA MATA PELAJARAN MATEMATIKA MATERI PERKALIAN DI KELAS III SD ISLAM COKROAMINOTO - Sri Adisti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The objectives of this study are: 1) To design and develop an educational game for mathematics subjects focusing on multiplication material; 2) To test the feasibility of the educational game and assist students in understanding multiplication. This research uses the Research and Development (R&D) method with the ADDIE development model. Data collection techniques include interviews, questionnaires, and documentation, combined with Black Box Testing and product feasibility validation by experts to provide feedback regarding the feasibility of the educational game. The product feasibility validation was analyzed and converted using the Likert Scale. The results of the study show that the educational game received a “highly feasible” criterion according to media experts with an average percentage of 85.71%; according to material experts, it obtained an average of 95.83% with a “highly feasible” criterion; and according to educators, it gained an average of 96.11% with a “highly feasible” criterion. Therefore, the “PEKA” game is feasible to be used as a learning medium and as entertainment for studying anywhere and anytime.